Konservasi Penyu Lekang (Lepidochelys Olivacea) untuk Menyelamatkan Ekosistem Alam di Pantai Lowita Kec. Suppa, Kab. Pinrang - Muh. Rapi; Hamsa, Syamsul; Sofyan; Fadillah Adjeng Kusumastuti Ary Putri; Bau’ Febrianti Laisa; Rahmayana; Juwaeria Nur Aprilyanti; Budiarty Dia Rezkita (KHIDMAH: Jurnal Pengabdian Masyarakat, 2024)
Lowita Beach is an area where many turtle species are found. Local people hunt and trade turtle meat and eggs. The aim of this activity is to participate in turtle conservation activities at Lowita Beach, Suppa District, Pinrang Regency. The method used in the activity was to take part in turtle activities managed by the Lima Putra Pesisir community at Lowita Beach, Suppa District, Pinrang Regency. Indicators of the effectiveness of turtle conservation activities can be seen from the implementation of activities in the form of; beach monitoring with patrols, egg origin, hatching success, turtle breeding and hatchling release. Steps for olive ridley turtle conservation activities include; 1) opening, 2) presentation of material by the Five Coastal Sons Community, 3) patrol on Lowita beach, 4) releasing turtles on Lowita beach, 5) cleaning of Lowita beach. Activities that have been carried out in turtle conservation are 1) observing eggs being incubated on special land, 2) obtaining turtle conservation materials by the Lima Putra Pesisir Community, 3) carrying out patrols on Lowita beach to save eggs from humans, monitor lizards and dogs, 4) releasing turtles on the beach in the morning from 07.00 – 08.00 WITA.